Protective Forests As Ecosystem-based Solution for Disaster Risk Reduction (Eco-DRR) - Michaela Teich; Cristian Accastello; Frank Perzl; Karl Kleemayr (IntechOpen, 2022)
Protective forests are a key component to reduce natural hazard risks in mountain areas by preventing or decreasing the frequency, magnitude and/or intensity of snow avalanches, rockfall, landslides, floods, and debris flows. This book summarizes the state-of-the-art knowledge and introduces methods and decision support tools to facilitate the use of protective forests for Ecosystem-based Disaster Risk Reduction (Eco-DRR) as part of an integrated risk management in the Alpine Space. Moreover, it highlights how translating scientific knowledge into practical solutions can only be achieved by an active and iterative exchange with practitioners and policy makers, and a common understanding of applied concepts and definitions. Only then can protective forests be managed sustainably under constantly changing climate and socio-economic conditions.